The level of perceived quality and safety of health services by recipients. Recommendations and inter- ventions for health care policies - Foteini Koulouri; George Anastopoulos; George Avramidis; Dimitrios Skoutelis (Ellīniko Periodiko tīs Nosīleutikīs Epistīmīs, 2017)
In recent years, the importance of the quality in health sector is more and more acknowledged. In broader terms the literature on quality in health care contributed to this, and stressed the importance of meeting the needs of the service recipient. Safety and quality in health care constitute a multi-dimensional parameter and involve many factors and various resources. Safety is positively associated to the quality, as the existence of the one ensures the improvement of the other. Thus, there is a great effort to create a framework, through guidelines and instructions that could contribute to the protection and development of quality and safety. It is important that this framework includes many features that have been expressed as requests by the patients themselves and which can contribute to the development of realistic and effective recommendations for improvement. Greek reality reveals certain gaps in safety and quality of services delivered, so the main attention has to be focused on developing an integral national health policy; the development of guidelines and the appropriate evaluation of their implementation could be a first effective approach. Formulating an institutional framework about safety and quality in health sector should be incorporated in the culture of all health organizations. To this end, the involvement of health professionals is a vital and strategic point. Health care practitioners should incorporate safety and quality culture in their daily routine and health managers should enact efficient ways of evaluation and control mechanisms in order to achieve better outcomes. Motivation to this direction and active participation should be encouraged with positive approaches, away from any kind of sanction. Any mistakes, adverse effects and deviations should be identified, reported, analyzed and formulate the base of the corrective action. In conclusion, safety and quality in health sector are essential and strongly associated with health services users’ satisfaction and quality of life; thus stakeholders and health professionals should focus on these basic conditions in order to achieve the “Health for All” goals in a national, international and universal perspective